The effective coping strategies against burnout: perceptions of Pakistani medical students. - Maryam Abbasi; Mohammad Al Eraky; Rahila Yasmeen; Rabia Ashfaq (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the effective coping strategies used by medical students against burnout. Method: The study was a mixed method study design. The Maslach burnout inventory (MBI) was used to identify burnout after which focus group discussions were carried out. Results: In our study, 56% of the students had high levels of Emotional Exhaustion, 23% had moderate and 21 % has low levels of EE, on the Cynicism scale 63% scored high,32% scored moderate while 5% scored low on cynicism scale. For professional efficacy 28% students scored low,50% scored moderate and 22% scored high on professional efficacy scale. Students with high scores on EE and Cynicism and low scores on Professional Efficacy were considered as burnt out. To determine coping strategies, focus group discussions and interviews with students with high burnout and low burnout were carried out. Seeking emotional support for coping was very common in the high burn out group. This involved getting moral support, sympathy and understanding. Parents played the main role in providing support to these students. Turning to religion, acceptance and venting were also seen as commonly used coping strategies. In the low burn out group, friends were the main source of support. Turning to religion was also found in this group. Doing extracurricular activities, positive reinterpretation and mental disengagement were also used to cope with stressful events. Conclusion: The results of this study can be used to promote positive coping strategies in students who are suffering from or at risk of developing burnout. Continuous...